The specifics of developing the social intelligence of Oralman students with artificial intelligence - Dyussenova, Alua; Mandykayeva, Almagul; Mambetalina, Aliya; Menlibekova, Gulbakhyt; Aitysheva, Aigul; Nurkatov, Yerbol (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examines the impact of an educational program based on artificial intelligence (AI) on improving social intelligence among Oralman students (a group of repatriates from among ethnic Kazakhs who faced unique integration problems in Kazakhstan). The main objective was to assess whether targeted interventions can effectively improve social skills that are crucial for successful social integration. The study involved 300 students aged 20 to 22 years, divided into experimental and control groups. Students participated in a six-month AI program designed to develop social intelligence using interactive tools and modeling. Pre-test and post-test assessments used the Tromso social intelligence scale (TSIS), focusing on areas such as social information processing, social skills, and social awareness. Following the intervention, the outcomes revealed that the experimental group had made notable progress in every area that was examined. Specifically, in this group, the overall score increased significantly from 59.37 to 82.33, and the average post-test scores climbed to 25.87 for social information processing, 27.33 for social skills, and 29.13 for social awareness. On the contrary, minimal changes observed in the scores of the control group emphasize the effectiveness of the AI-based program. The analysis of secondary data further confirmed the results: t-tests showed statistically significant differences in the post-test scores between the groups. The progress of the experimental group highlights the potential of AI-based educational tools in the development of basic social competencies, offering promising opportunities to support the integration of Oralman students into Kazakh society.